Efektifitas Assertiveness Training untuk Siswa Sekolah Menengah Pertama (SMP) - Dini Ayu Indraswari; Moh. Irtadji; Ike Dwiastuti (Universitas Andalas, 2017)
Abstract. This research is aimed to improve early adolescent student’s assertiveness. Hypotheses in this research is . Experimental research design is used by implementing randomized pretest-posttest control group design. The subjects are students of VIII SMPK at Malang, 30 students for experimental group and 30 students for control group. Assertiveness scale is used to measure the level of assertiveness which has 27 items with the realibility index is 0,729. Assertiveness training module has been written as the procedure to guide its process. Paired sample t-test and independent sample t-test are used to analyze the data. The results show significance score 0,000 < 0,005 that means there are differences between pretest-posttest and groups. Moreover, the effect size result shows 0,93 that means the treatment gives a big effect for student’s assertiveness. Therefore, it can be concluded that assertiveness training is effective to improve student’s assertiveness.